2013
DOI: 10.1136/jnnp-2013-306509
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre prospective study of Guillain-Barré Syndrome in Japan: a focus on the incidence of subtypes

Abstract: The frequency of GBS patients with the electrodiagnosis of AMAN by single nerve conduction studies is approximately 20% in Japan, and the AMAN pattern is closely associated with anti-GM1 antibodies. The incidence of FS appears to be much higher in Japan than in Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
36
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
10
36
1
5
Order By: Relevance
“…On the other hand, a single‐hospital study conducted in Taiwan reported that the frequency of FS cases relative to all GBS + FS cases was 18%–19% . Japanese researchers found that FS accounted for 26% or 34% of all GBS + FS cases . Our results are in agreement with the previous finding that FS has a higher occurrence in Asia than in Europe.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a single‐hospital study conducted in Taiwan reported that the frequency of FS cases relative to all GBS + FS cases was 18%–19% . Japanese researchers found that FS accounted for 26% or 34% of all GBS + FS cases . Our results are in agreement with the previous finding that FS has a higher occurrence in Asia than in Europe.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that regional differences exist between AMAN and AIDP; nevertheless, AMAN is not always uncommon in East Asia [1]. Our data are in partial agreement with a recent Japanese report of the predominance of AIDP [15]. Indeed, the sequential electrophysiological test up to 6 weeks after the onset of GBS was not performed in all patients.…”
Section: Discussionsupporting
confidence: 90%
“…13 In contrast, facial weakness is seen in 60% of GBS patients in the West. 1 In our study, facial weakness developed in 54% of AIDP and 23% of AMAN patients, statistically more frequent in AIDP than AMAN.…”
Section: Discussionmentioning
confidence: 95%
“…12 A multicenter study over 3 years at 23 hospitals in Japan found 184 GBS and 79 MFS patients, and the proportion of MFS to GBS was 43%. 13 These studies suggest a higher incidence of MFS in Japan compared to the West (about 5% of GBS), 1 although further epidemiological studies are needed to determine the exact incidence of each condition.…”
Section: Discussionmentioning
confidence: 97%
“…Additional recent studies, including a comprehensive analysis of serum antibodies from 199 patients in 3 countries, have shown a significant association of AMAN with anti-GM1 antibodies. [40][41][42] Although the role of these antibodies in the pathophysiology of GBS has not been clearly defined, because they have been localized to the nodal axolemma before axonal degeneration, 32,43 it has been proposed that they may initiate an immune attack on the axolemma 43 or cause a conduction blockade. 44 Autonomic dysfunction, largely excessive sympathetic symptoms such as sinus tachycardia, has long been described in GBS.…”
Section: Discussionmentioning
confidence: 99%